PENGARUH MOTIVASI BELAJAR SISWA DAN MEDIA PEMBELAJARAN DENGAN MENGGUNAKAN LCD TERHADAP PRESTASI BELAJAR SISWA KELAS XI MATA PELAJARAN BAHASA INGGRIS DI SMA NEGERI 3 KOTA PROBOLINGGO - Hery Susilo (Jurnal Penelitian dan Pendidikan IPS, 2016)
This research aims to know the influence of learning motivation and instructional media using LCD toward English learning achievement of tenth graders at SMA Negeri 3 Probolinggo. Sixty (60) students were randomly invoked as participants of this research from five classes. The results showed that learning motivation, instructional media, and both influenced students’ English learning achievement significantly.